Perubahan Sistem Politik Kerajaan Sawitto Pasca Perlawanan terhadap Kolonial Belanda (1905-1906) - Zulfahmi; Musyarif; A. Nurkidam (Universitas Islam Negeri Alauddin Makassar, 2024)
This study focuses on the Sawitto Kingdom’s resistance against the Dutch colonial government, emphasizing the conflict process between the kingdom and the colonial administration, as well as the impacts of that resistance. To examine this, the author employs a historical method consisting of four stages: data collection (heuristics), source criticism, interpretation, and historiography, with socio-political analysis. This research reveals that Sawitto's resistance in the early 20th century was driven not only by opposition to the mandatory taxed port policy that imposed import, export, and harbor duties but also by Dutch colonial interference in Sawitto's domestic affairs. Ultimately, the conflict was won by the Dutch Colonial Government, marking the integration of colonial power in Sawitto. This resulted in changes to the local political system, including the Dutch assumption of royal authority and the reduction of the Sawitto king’s role to a symbolic figure.